The treatment of advanced lung adenocarcinoma with activating EGFR mutations. (12th December 2021) - Rocco, Danilo; Della Gravara, Luigi; Battiloro, Ciro; Maione, Paolo; Gridelli, Cesare
ABSTRACT: Introduction: Lung adenocarcinomas account for approximately 40–50% of all NSCLC (Non-Small Cell Lung Cancer) cases. In addition, lung adenocarcinomas can harbor several different genetic mutations, EGFR (Epidermal Growth Factor Receptor) being the most frequent one, accounting for approximately 5–15% of all the mutations in western patients and for approximately 40–55% in Asian patients; on the other hand, EGFR mutations are uncommon in squamous histology. Approximately 90% of EGFR mutations are represented by exon 19 in-frame deletion and by the L858R exon 21-point mutation, that confer sensitivity to EGFR TKI (Tyrosine Kinase Inhibitors) treatment. Areas covered: The authors comprehensively review the current state of the art with reference to EGFR+ NSCLC treatment and to discuss the possible future developments. Expert opinion: Osimertinib must be considered the preferred first-line agent in EGFR+ advanced NSCLC patients thanks to its superior performances. With respect to acquired resistance mechanisms to osimertinib, the currently ongoing clinical trials will surely help us to better understand and tackle them. Globally, we strongly believe that a biomarker-driven sequential treatment algorithm is key in order to provide personalized, effective and durable therapies in the increasingly complex landscape of EGFR+ advanced NSCLC.